Need satisfaction as the mediator in the relationship between psychological capital and foreign language anxiety among senior high school students in Guizhou, China - Huang, Ying; Burhanuddin, Nur Aimi Nasuha; Liu, Zhishan (Human Resource Management Academic Research Society, 2024)
This study explores the relationship between psychological capital (PsyCap) and foreign language anxiety in academic settings, with need satisfaction as the mediator in this relationship. Since the emergence of the concept of PsyCap, a wealth of research has focused on the workplace domain, demonstrating its positive impact on work outcomes. However, its effectiveness in language learning and the potential benefits it might offer in alleviating foreign language anxiety, especially in non-Western contexts, have yet to be thoroughly investigated. Therefore, the study aims to fill the academic gap regarding PsyCap, exploring the pathways and relationships between PsyCap and foreign language anxiety, and based on the Self-Determination Theory, selecting need satisfaction as a mediator to help explain this relationship. In this study, the relationship will be investigated using the explanatory sequential design method. A quantitative study will be conducted first to collect data on high school students’ psychological capital, foreign language anxiety, and need satisfaction levels. Then, a qualitative study will be undertaken to analyze the relationship in depth after verifying the hypothesis that there is a correlation between the three.